Perceived Social Support and Well-Being of International Students at an Italian University - Cipolletta, Sabrina; Mercurio, Arianna; Pezzetta, Rachele (Journal of International Students, 2021)
The present study aimed to explore international students’ well-being in relation to their perception of social support and dispersion of dependency on various resources. Participants were 139 international students at an Italian university who completed the WHO-5 Well-being Index, Symptom Checklist 90-R, Multidimensional Scale of Perceived Social Support, and Dependency Grids. Results showed that higher well-being correlated with higher support and lower distress and that higher dispersion of dependency was associated with higher perceived support. International students who sought professional psychological help also reported lower well-being, higher distress, and fewer resources compared to those who did not seek psychological support. Furthermore, coming from collectivist cultures (rather than individualist ones) as well as being a long-term (rather than short-term) student was mostly associated with higher distress and less perceived support. These results suggest that counselling services for international students should help them find new sources of social support.